2014
DOI: 10.1007/s11517-014-1205-3
|View full text |Cite
|
Sign up to set email alerts
|

Continuous flow left ventricular pump support and its effect on regional left ventricular wall stress: finite element analysis study

Abstract: Left ventricular assist device (LVAD) support unloads left ventricular (LV) pressure and volume and decreases wall stress. This study investigated the effect of systematic LVAD unloading on the 3-dimensional myocardial wall stress by employing finite element models containing layered fiber structure, active contractility, and passive stiffness. The HeartMate II(®) (Thoratec, Inc., Pleasanton, CA) was used for LV unloading. The model geometries and hemodynamic conditions for baseline (BL) and LVAD support (LVsu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The most dramatic improvement, however, was seen in the reduction of pressure, chamber size and stress in the LV at ED. The reduction in chamber size and LV preload due to LVADs is well established in clinical findings ( 33 , 34 ) and other numerical investigations ( 18 , 32 , 35 ).…”
Section: Discussionmentioning
confidence: 75%
“…The most dramatic improvement, however, was seen in the reduction of pressure, chamber size and stress in the LV at ED. The reduction in chamber size and LV preload due to LVADs is well established in clinical findings ( 33 , 34 ) and other numerical investigations ( 18 , 32 , 35 ).…”
Section: Discussionmentioning
confidence: 75%
“…Clearly, a knowledge of mechanical engineering is needed to design and build these pumps, but it is also important to understand the ways in which LVADs alter the mechanics of the heart. LVADs modulate the wall stresses in the myocardial tissue, but also the flow patterns of the blood through the heart and into the aorta which can lead to clinical complications (21, 88) LVADs decrease the filling pressure and mechanical load on the ventricle which can reduce adverse remodeling (51). It has been shown that LVAD devices can reduce the expression of MMP-1 and MMP-9, increase the expression of TIMP-1 and TIMP-3, and decrease the expression of NF-κB (59, 109), Further, LVAD therapy has been shown to prevent myocyte hypertrophy (8).…”
Section: Biomechanics Of Cardiac Function Post-mimentioning
confidence: 99%
“…LVAD is found to reduce myocardial force by pumping blood out of the left ventricle. Jhun et al [ 32 ] investigated the changes in myocardial force under LVAD support by using computational fluid dynamic analysis (CFD). He found that the myocardial force under LVAD support was significantly reduced.…”
Section: Discussionmentioning
confidence: 99%